Computer-aided Structure prediction of Bluetongue Virus coat protein VP2 assisted by Optimized Potential for Liquid Simulations(OPLS) - Prajapati, Leena; Khandelwal, Ravina; Yogalakshmi, Kadapakkam Nandabalan; Munshi, Anjana; Nayarisseri, Anuraj (Current topics in medicinal chemistry, 2020)
The capsid coated protein of Bluetongue virus (BTV) VP2 is responsible for BTV transmission by the Culicoides vector to vertebrate hosts. Besides, VP2 is responsible for BTV entry into permissive cells and hence plays a major role in disease progression. However, its mechanism of action is still unknown. The present investigation aimed to predict the 3D structure of Viral Protein 2 of bluetongue virus assisted by Optimized Potential for Liquid Simulations (OPLS), structure validation, and an active site prediction. The 3D structure of the VP2 protein was built using a Python-based Computational algorithm. The templates were identified using Smith waterman’s Local alignment. The VP2 protein structure validated using PROCHECK. Molecular Dynamics Simulation (MDS) studies were performed using an academic software Desmond, Schrodinger dynamics for determining the stability of a model protein. The Ligand-Binding site was predicted by structure comparison using homology search and protein-protein network analysis, to reveals their stability and inhibition mechanism followed by the active site identification. The secondary structure of the VP2 reveals that the protein contains 220 Alpha Helix atoms, 40310Helix, 151 Beta sheets, 134 coils and 424 turns, whereas the 3D structure of Viral Protein 2 of BTV found to have 15774 total atoms in the structure. However, 961 amino acids were found in the final model. The dynamical crosscorrelation matrix (DCCM) analysis tool identifies putative protein domains and also confirms the stability of the predicted model and their dynamical behavior difference with the correlative fluctuations in motion. The biological interpretation of the Viral Protein 2 was carried out. DCCM maps were calculated, using a different coordinate reference frame, through which, protein domain boundaries and protein domain residue constituents were identified. The obtained model shows good reliability. Moreover, we anticipated that this research should play a promising role in the identification of novel candidates with the target protein to inhibit their functional significance.